Determinants of Sustainability Reporting Quality in Indonesia - Larassati, Tiyani; Juliardi, Dodik; Pujiningsih, Sri (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2024)
This study aims to investigate the effect of corporate integrity, external assurance, foreign ownership structure, audit committee size and meetings on the quality of sustainability reporting. The sample in this study is public companies listed on the Indonesia Stock Exchange from 2021 to 2022. This study uses Random Effect Model panel regression. The results showed that corporate integrity, external assurance, and audit committee meetings have a positive impact. Foreign ownership structure and audit committee size have no effect. Limitations in this study, first, the potential influence on the quality of sustainability reporting is not limited to the variables tested in this study. Further research can be conducted on new determinants, such as corporate vision and/or mission, organizational culture, management competencies, and market pressures. Second, this research only uses quantitative methods, further research can use qualitative methods. This study has theoretical implications to add to the legitimacy theory literature in explaining the relationship between variables. Practical implications, for company managers can apply the principles of corporate integrity, consider external assurance services and increase the number of audit committee meetings. Regulators are expected to play an active role in drafting regulations related to upholding the principles of integrity, using external assurance services and organizing audit committee meetings. This research emphasizes quality over quantity. This study is also the first research in the Indonesian context to investigate the role of corporate integrity and involve the choice of external assurance service providers as a proxy.